Yield Performance and Heavy Metals Uptake of Solanum lycopersicum, Inoculated with Pseudomonas aeruginosa and Trichoderma harzianum - Salami, Abiodun Olusola; Adebiyi, Kehinde Adeyinka (Archives of Current Research International, 2017)
The study was conducted to investigate the yield performance and heavy metals uptake of Solanum lycopersicum irrigated with contaminated stream water. For this purpose tomato plants was cultivated in soil irrigated with heavy metals contaminated stream water. Heavy metals content of the plant and yield performance of plant were examined. The heavy metal contaminated stream water was found to load the soil with heavy metals (Fe, Zn, Cu and Pb). The soil were treated with Pseudomonas aeruginosa and Trichoderma harzianum. The organisms was inoculated singly or in combination into experimental pots containing 3000 g of sterilized soil. Seeds of Solanum lycopersicum were raised in nursery for a period of 3 weeks and the treatments were applied before transplanting into experimental pots. Atomic Absorption Spectroscopy (AAS) method was used for detecting the amount of heavy metal in the stream before the experiment commenced. The heavy metals contaminated stream water was applied to the plants in measured quantities; 0, 5 and 10%. Yield data from the experiment were recorded and heavy metal uptake by the tomato plants were detected using the AAS method. It was evident from this experiment the plants treated with no inoculation of Psedomonas aeruginosa and/or Trichorderma harzianum produced lower yield and higher concentration of heavy metals in the harvested fruits. Plants treated with Pseudomonas aeruginosa produced better yield and lower concentration of heavy metals in the harvested fruits than other treatments applied at all levels of contaminated stream water sample. From this study, it can be concluded that the use of contaminated stream water could be a possible source of heavy metals in tomato and could pose danger to human health. The use of microorganisms for the treatment of heavy metals contaminated soil was effective for the growth and productivity of tomato.